Study of Health-Related Quality of Life and Healthcare Utilization among Type 2 Diabetic Population in an Urban Area of Eastern Nepal - Sangita Shah; Nilambar Jha; Deepak Kumar Yadav; Prajjwal Pyakurel; Sanjib Kumar Sharma; Suman Bahadur Singh (International Journal of Endocrinology)
Introduction. Diabetes mellitus is a major cause of morbidity and mortality and places huge burden on public health funding. Diabetes affects quality of life through associated complications, comorbidity, and disease burden. Consequently, people have frequent healthcare visits. This study assessed quality of life and healthcare utilization patterns among type 2 diabetic populations in an urban area of eastern Nepal. Methods. A cross-sectional study was conducted among 270 participants of age ≥20 years with type 2 diabetes in Itahari using a semistructured questionnaire. A D-39 questionnaire was used to assess quality of life. Five wards were selected by systematic random sampling, and the population was proportionate according to the sample size. Multiple linear regressions were conducted to identify the factors associated with quality of life and its domains. Results. The highest mean score ± SD was found in the domain anxiety and worry (57.34 ± 11.08). About 18.5% of the participants perceived extremely affected quality of life. Hypertension (55.55%) was the most common comorbidity. Age, marital status, literacy, alcohol, disease duration, comorbidity, and complications were significantly associated with overall quality of life. In last 6 months of duration, 93.7% had hospital visits. Among them, 8.1% had emergency visit and 5.9% were admitted in the hospital. Conclusion. People with diabetes in this study were more affected in the domain anxiety and worry. The frequency of healthcare access and utilization in patients with type 2 diabetes was high. The quality of life among them could be improved by taking care on healthy behavior, comorbid conditions, and complications.